Smart Agriculture 4.0: Technology Recommendations and Interoperability of Devices, Sensors and Data Management Using Blockchain - Kaschel-Carcamo, H; Adasme-Soto, P; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2022)
Currently the protocols associated with wireless technologies applied to Wireless Sensor Networks (WSN) is a great alternative that will allow the control, monitoring and of course the marketing of plant products. In the context of intelligent agriculture, since it is intended to obtain a higher degree of productivity, allowing great benefits that are associated with crops and harvests. It also describes the parameters of each wireless communication protocol, which are classified according to coverage, as well as how Blockchain interacts in data management in different activities in smart agriculture. The article provides the fundamental technical specifications of the protocols for wireless networks, consequently, it will be possible to have a global technical vision, which will allow the selection of devices and/or sensors now of implementing a WSN applied to smart agriculture, according to requirements. © 2022 IEEE.